THE EFFECTIVENESS OF TEACHING IMPORTANT SKILLS OF ENGLISH LANGUAGE TO PRIMARY CHOOL LEARNERS THROUGH GAMES (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Contemporary pedagogical approaches to language acquisition for young learners prioritize flexible and effective methods, with game-based instruction emerging as a particularly valuable and increasingly prevalent technique. This article examines several effective game-based strategies designed to comprehensively address various aspects of language development in young children.